Achalasia: outcome of patients treated with intrasphincteric injection of botulinum toxin. Issue 1 (July 1997) - Cuillière, C; Ducrotté, P; Zerbib, F; Metman, E H; de Looze, D; Guillemot, F; Hudziak, H; Lamouliatte, H; Grimaud, J C; Ropert, A; Dapoigny, M; Bost, R; et al.
Abstract : BACKGROUND: To evaluate the safety and clinical efficacy of botulinum toxin (BT) in patients with achalasia followed up for six months. METHODS: Fifty five symptomatic patients with manometrically proven achalasia were included in a multicentre prospective trial. Before and two weeks and two months after intrasphincteric injection of BT, symptoms of dysphagia, regurgitation, and chest pain were scored on a 0-3 scale, and lower oesophageal sphincter pressure (LOSP) was assessed. The symptom score was determined again at six months, clinical improvement being defined by < or = 3, relapse by > 3, and failure as a relapse after two injections or loss to follow up. RESULTS: Except for transient chest or epigastric pain (22%), no side effects were observed. There was a significant decrease in LOSP after treatment. Symptom scores were significantly improved at two weeks (2.0 (SD 1.6)), two months (1.7 (1.8)), and six months (1.9 (2.0)) compared with pretreatment values (5.1 (1.8), p < 0.001). At six months, 33 patients had clinical improvement (27 after one injection), 17 were considered failures, and five had just relapsed. Although there was a trend for age (older patients being more responsive), age, sex, prior duration of symptoms, initial symptom score, weight loss, LOSP, magnitude of oesophageal contractions, vigorous or non-vigorous achalasia, previous dilatations, and radiological features were not predictive of results. CONCLUSIONS: This multicentre series confirms that intrasphincteric injection of BT is a safe procedure, resulting in clinical improvement in 60% of patients with achalasia at six months. The therapeutic role of BT in achalasia needs further evaluation with regard to other alternatives.